2013
DOI: 10.1111/1471-0528.12196
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery pulsatility index improves prediction of methotrexate resistance in women with gestational trophoblastic neoplasia with FIGO score 5–6

Abstract: Objective The Uterine Artery Pulsatility Index (UAPI) is an ultrasound measure of tumour vascularity. In this study, we hypothesised that a UAPI 1 (high vascularity) would identify women with gestational trophoblastic neoplasia (GTN) at increased risk of resistance to first-line single-agent methotrexate (MTX-R).Design Single-centre cohort study.Setting Charing Cross Hospital, a UK national centre for the treatment of trophoblastic disease.Population All women with a GTN FIGO score 5-6 treated with methotrexat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 5 publications
(11 reference statements)
2
25
0
Order By: Relevance
“…Keeping in view the documented role of VEGF , EGFR , and c‐jun in enhancing invasion and metastasis in tumorogenesis and the presence of higher vascular density demonstrated by these disorders, the observed high expression of these genes in molar pregnancies and choriocarcinoma cells observed in this study, suggest their role in contributing towards the pathogenesis of GTDs.…”
Section: Discussionsupporting
confidence: 55%
“…Keeping in view the documented role of VEGF , EGFR , and c‐jun in enhancing invasion and metastasis in tumorogenesis and the presence of higher vascular density demonstrated by these disorders, the observed high expression of these genes in molar pregnancies and choriocarcinoma cells observed in this study, suggest their role in contributing towards the pathogenesis of GTDs.…”
Section: Discussionsupporting
confidence: 55%
“…When there is no response to sequential single-agent therapy, multiagent ChT should be initiated, and the EMA-CO regimen is the most commonly used multiagent ChT 4 . Recent studies suggest that a uterine artery pulsatility index equal to or lower than one predicts an increase in the risk of resistance to MTX/FA in women with low-risk GTN and may be useful in patient staging for first line therapy 44,45 . Prospective studies are underway evaluate this finding.…”
Section: Resistant or Recurrent Diseasementioning
confidence: 99%
“…Recently published studies by Agarwal et al [17] and Sita-Lumsden [18] have revalidated the usefulness of uterine artery PI (UAPI) as a predictor of methotrexate resistance (MTX-R) independent of Charing Cross Hospital and FIGO scores. The risk of MTX-R in patients with a FIGO score of 6 and UAPI was shown to be 100% versus 20% in patients with PI > 1 ( χ 2    P < 0.0001) by Agarwal et al Sita-Lumsden et al showed that UAPI ≤ 1 predicted MTX-R independent of the FIGO score (hazard ratio 2.9, P = 0.04), with an absolute risk of MTX-R in women with a UAPI ≤ 1 of 67% (95% CI 53–79%) compared with 42% (95% CI 24–61%) with a UAPI > 1 ( P = 0.036).…”
Section: Imaging Features Of the Uterine Diseasementioning
confidence: 99%